Vitamin D rescues dysfunction of fetal endothelial colony forming cells from individuals with gestational diabetes. Issue 4 (April 2015) - Gui, J.; Rohrbach, A.; Borns, K.; Hillemanns, P.; Feng, L.; Hubel, C.A.; von Versen-Höynck, F.
Abstract Introduction Gestational diabetes (GDM) is associated with long-term cardiovascular and metabolic diseases in offspring. However, the mechanisms are not well understood. We explored whether fetal exposure to a diabetic environment is associated with fetal endothelial progenitor cell dysfunction, and whether vitamin D can reverse the impairment. Methods Nineteen women with uncomplicated pregnancies and 18 women with GDM were recruited before delivery. Time to first appearance of endothelial colony forming cell (ECFC) colonies and number of ECFC colonies formed from culture of cord peripheral blood mononuclear cells were determined. Angiogenesis-related functions of ECFCs in vitro were tested in the presence or absence of vitamin D. Results Fetal ECFCs from GDM pregnancies formed fewer colonies in culture (P = 0.04) and displayed reduced proliferation (P = 0.02), migration (P = 0.04) and tubule formation (P = 0.03) compared to uncomplicated pregnancies. Fetal ECFCs exposed to hyperglycemia in vitro exhibited less migration (P < 0.05) and less tubule formation (P < 0.05) than normoglycemic control. Vitamin D significantly improved the dysfunction of fetal ECFCs from pregnancies complicated by GDM or after exposure of healthy ECFCs to hyperglycemia. Discussion Fetal ECFCs from GDM pregnancies or ECFCs exposed to hyperglycemia in vitro exhibit reduced quantity and impaired angiogenesis-related functions. Vitamin D significantly rescues these functions. These findings may have implications for vascular function of infants exposed to a diabetic intrauterine environment.